Кореляція текст / дискурс у дослідженнях сучасних французьких художніх прозових творів - Філоненко, Наталія Геогріївна; Filonenko ., N. H (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено проблему співвідношення понять текст і дискурс у вітчизняних і зарубіжних дослід¬женнях сучасних художніх прозових текстів крізь призму позицій автора та читача. Увагу зосереджено на соціокультурних та історичних особливостях французької літератури сьогодення. Доводиться необхідність врахування результатів аналізу дискурсивних характеристик у розвідках художніх прозових текстів, уста¬новлюються відмінності та спільні риси художнього тексту і художнього дискурсу, розкриваються авторський і читацький модуси взаємодії з художнім текстом на підставі визначення його комунікативної ситуації. The article highlighted the problem of relations between concepts text and discourse in domestic and foreign studies of modern literary prose texts through the prism of the author and the reader. The focus is on the social, cultural and historical features of the current French literature. The necessity of taking into account the characteristics of the analysis of discourse in studies of literary prose texts is proved. The article defines the differences and similarities of literary text and literary discourse, and reveals the author and reader modes of interaction with literary text on the basis of the definition of the communicative situation of a literary text. The concept of «artistic text» and «artistic discourse» in studies of art prose texts are not opposed to each other, they are neither identical nor dummy. Communicative situation of literary discourse involves the author and the reader's contact with the artistic text and through artistic text. Taking into account the features of artistic discourse and combining approaches in the study of textual language units of modern French literary prose texts is necessary because the process is dictated by the specific literature in France. The value of discourse and text features becomes relevant not only in line with the concept of postmodernism, but in modern French literature in general.
Correlation text / discourse of the modern French prose works of art
Keywords: художній текст; artistic text; художній дискурс; artistic discourse; прагматика автора; author’s pragmatics